PENGEMBANGAN DAN IMPLEMENTASI MOODLE SELF HOSTED SEBAGAI E-LEARNING MANDIRI SEKOLAH DALAM MENUNJANG MODEL PEMBELAJRAN BLENDED LEARNING DI SMP NEGERI 1 PAJO - Rahmatul Rizky; Syahrul (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2022)
This study aims to produce an e-learning Portal based on Moodle Self-Hosted as a virtual classroom for various activities such as uploading and downloading subject matter, assignments, quizzes, as well as conducting attendance and video conferencing between teachers and students. This system is based on a website that is connected to Moodle Mobile Apps on Android and iOS operating systems. This research is Research and Development (R&D) research with ADDIE development model which consists of several stages, namely analysis, design, development, implementation and evaluation of the system. The results of this study are (1) the implementation of online learning using the web-based and mobile-based Moodle Self-Hosted e-learning portal.(2) The results of application testing using the ISO 25010 standard on aspects of functional suitability, performance efficiency, compatibility and portability have good quality. (3) The Moodle Self-Hosted e-learning portal received a very decent response from users based on software testing using the ISO 25010 standard on usability aspects